Обзор классификаций внутрипротоковых папиллярных муцинозных неоплазий, показаний к хирургическому вмешательству и его результатов - Đorđević V.; Markovic M.; Protić M.; Knežević Đ.; Basarić D.; Antovikj S.; Grubor N.; Radenković D. (VIDAR Publishing House, 2025)
Intraductal papillary mucinous neoplasms (IPMNs) are pancreatic cystic lesions with malignant potential. This review outlines current guidelines, surgical indications, outcomes, and surveillance strategies. It also highlights recent advances in minimally invasive surgery and emerging biomarkers aimed at improving risk stratification and reducing unnecessary resections.
A Review of Introductal Papillary Mucinous Neoplasia Classification, Surgical Indications, and Outcomes
Keywords: intraductal papillary mucinous neoplasms (IPMN); surgery; indications to pancreatic surgery; outcomes after pancreatic surgery